G533(P) Neonatal Readmission Audit. (7th April 2014) - Damda, F; Zerb, T; Field, A; Rogerson, K; Chukwudi, N
Abstract : Background: Preventable neonatal admissions are an unnecessary expense to hospital trusts, a traumatic experience for families and put neonates at increased risk of hospital acquired infection. Aims: To assess the incidence of neonatal readmissions to a London paediatric department and to analyse the diagnosis & management of neonates re-admitted with feeding problems. From this we aim to observe any correlation between length of birth stay and length of readmission stay. Methods: A retrospective audit was conducted on all infants (≤ 28 days) that were readmitted between Oct 2011–Oct 2012. A review of the paper notes and discharge summaries was carried out for all those with a primary diagnosis code including 'feeding'. Results: A total of 266 (8% of a total of 3308 paediatric admissions) neonates were re-admitted over 13 month period. 42 had a primary diagnosis of feeding problems. 36 of these notes were available for analysing. 26 (72%) readmitted under 1 week of age. The 3 most common presenting complaints were reduced feeds, weight loss and jaundice. An organic cause was found in only 4 cases. There was a small positive correlation between length of birth stay and length of readmission stay. The most common intervention was a feeding plan given to 33 (92%), followed by feeding advice and counselling (22%) and antibiotics (17%). The admission versus discharge mode of feeding showed a drop in breast feeding from 61% to 3% and an increase in mixed feeding (breast and bottle) from 25% to 72%. Conclusion: Better community support around neonatal feeding particularly in the first week of life could reduce the number of preventable neonatal readmissions. Hospital based treatment for feeding problems is likely to result in a change in feeding method away from breastfeeding alone.